Sistem Rekomendasi Pemilihan Kinerja Koperasi Terbaik Menggunakan Simple Multi Attribute Rating Technique Method - Ahmad Bustomi (PT. Tech Cart Press, 2023)
Assessing the best cooperative involves several factors involving sustainability, operational success, and positive impact on its members. Cooperatives that are considered the best usually have transparent and accountable management, offer relevant and quality services and products, and have a high level of participation from their members. This study aims to apply the SMART Method in the recommendation system for selecting the best cooperatives in the XYZ Cooperative and MSME Office so that the Office gets a recommendation for selecting the best cooperative based on the SMART method. The ranking results of the table above show that the 1st rank of the best cooperative performance was obtained with a final value of 0.61 by Cooperative D, the 2nd rank of the best cooperative performance was obtained with a final value of 0.585 by Cooperative F, the 3rd rank of the best cooperative performance was obtained with a final value of 0.44 by Cooperative G.